Turbulent air-flow and dispersion of pollutants in the atmosphere - Epstein, Mario (1977)
This study is a contribution toward the understanding and prediction of turbulent dispersion of pollutants in the atmosphere. The main underlying assumption suggestion is that the Lagrangian autocorrelation RL used in computation of plume dispersion may be approximated by an Eulerian space-time correlation.